α-GLUCOSIDASE INHIBITORY EFFECT OF SULOCHRIN FROM ASPERGILLUSTERREUS AND ITSBROMINATED DERIVATIVES - Dewi, RiznaTriana; Darmawan, Akhmad; Mulyani, Hani; Puspa Dewi, N Lotulung; Minarti, Minarti; Megawati, Megawati (Malaysian Journal of Science, 2018)
Use of α-glucosidase inhibitorsis one of the therapeutic approaches for decreasing postprandial hyperglycemia. Sulochrin (1) from Aspergillus terreus as well as two synthetic sulochrin derivatives were assessed for antidiabetic activity against yeast and rat intestine α-glucosidase. Sulochrin showed potential inhibition against yeast α-glucosidase, through a non-competitive mode with an IC50 value of 133.79 µM, and rat intestine α-glucosidase by uncompetitive mode with an IC50 value of 144.59 µM.. Two synthetic derivatives of sulochrin were also prepared by bromination which resulted in dibromo-sulochrin (2) and tribromo-sulochrin (3). Preliminary SAR studies of sulochrin derivatives revealed that the yeast α-glucosidase inhibitory activity of compound 2 and 3 increased than 1 due to substitution of hydrogen atom with bromine with IC50 values of 122.65 and 49.08 µM, respectively. However, the inhibitory activity against rat intestine α-glucosidase of 2 and 3 was decreased compared to 1. To the best our knowledge, this is the first report of structure-activity relationship of sulochrin and its derivatives as α-glucosidase inhibitors. These results suggested that sulochrin can potentially be used as a lead compound to develop new α-glucosidase inhibitor from microorganisms. Keywords: Aspergillus terreus, α-glucosidase inhibitory activity, sulochrin, bromination